Tyramine-Mediated Activation of Sympathetic Nerves Inhibits Insulin Secretion in Humans - Gilliam, Lisa K.; Palmer, Jerry P.; Taborsky, Gerald J. (The journal of clinical endocrinology and metabolism, 2007)
Context: Older studies have shown that high doses of norepinephrine infused into human subjects can inhibit insulin secretion. Similar inhibition during electrical stimulation of sympathetic nerves in animals raises the possibility that the suppression of insulin secretion seen in humans could reflect a physiological effect of sympathetic nerves on islet β-cells. However, a direct test of the hypothesis that moderate and selective activation of these nerves is sufficient to inhibit insulin secretion in humans is lacking. Objective: We sought to test this hypothesis by releasing moderate amounts of endogenous norepinephrine selectively from the sympathetic nerves of normal human subjects by infusing them with low doses of the indirect sympathomimetic agent tyramine. Methods: During a single study visit, 11 healthy subjects received iv injections of arginine either alone or in combination with a low-dose tyramine infusion. Physiological (blood pressure) and biochemical (insulin, glucose, and norepinephrine) parameters were measured. Results: The acute insulin response to arginine was significantly reduced during tyramine compared with that seen in the absence of tyramine (P = 0.036). Conclusions: These data suggest that moderate and selective activation of sympathetic nerves inhibits insulin release in humans.